Clinical evaluation of Abbott and Wellcome enzyme linked immunosorbent assays for detection of serum antibodies to human immunodeficiency virus (HIV). Issue 5 (May 1987) - Evans, R P; Shanson, D C; Mortimer, P P
Abstract : Abbott and Wellcome enzyme linked immunosorbent assays (ELISAs) for detection of antibodies to human immunodeficiency virus (HIV) were compared in tests on 932 sera collected predominantly from male homosexuals attending a sexually transmitted disease (STD) clinic in central London. Two hundred and twenty three sera had HIV antibodies detected by both types of assay, with confirmation of the results by further tests carried out at the Virus Reference Laboratory (VRL) in Colindale. There was a 97.3% correlation between the results obtained by the two commercial ELISA assays on the tests carried out on unheated sera. The Abbott ELISA gave significantly more false positive results than the Wellcome test when the manufacturer's instructions for cut off values were followed. There was one false negative Abbott results: it failed to react to repeated Abbott ELISA but was positive by Wellcome and confirmatory assays. Of 283 heat treated sera 14.8% gave falsely reactive results with the Abbott assay whereas there were no differences between heated and unheated sera with the Wellcome assay. VRL or Western blot confirmatory assays, or both, confirmed all the 235 positive results obtained with the Wellcome assay.